A new approach to immunosuppressive therapy in patients with glomerulonephritis with nephrotic syndrome - S. I. Kudryashov; M. A. Stenina; L. M. Karzakova; T. S. Lutkova (Медицинская иммунология)
Glomerulonephritis (GN) is a group of immuno-inflammatory kidney diseases with predominant glomerular lesions that are difficult to treat. The greatest problems are caused by the treatment of GN with nephrotic syndrome, which often has a recurrent course. The aim of the research was to study the effectiveness of recombinant interleukin-2 (rIL-2) therapy in the GN patients with nephrotic syndrome. 62 patients with a nephrotic form of primary GN with frequent relapses admitted to the Nephrology Department have been recruited into the study. The age of patients was from 18 to 65 years. The patients underwent standard examinations, as well as immunological studies, before administration of the anti-relapse treatment, and 12 months after the treatment was started. Immunological testing included immunophenotyping of lymphocytes with counting of T and B lymphocytes, immunoregulatory and activated subpopulations of T lymphocytes, determination of urinary immunoglobulins (IgM, IgG, IgA) by immunoturbidimetric assays, proinflammatory cytokines – IL-1β, IL-8, IL-17A and anti-inflammatory cytokine IL-10 by ELISA tests. As a result of studies, the examined patients showed an increased contents of T helper cells, activated T lymphocytes (CD8+HLA-DR+CD45+, CD3+CD8brightCD38+) along with decreased numbers of Treg cells and an increased contents of proinflammatory cytokines IL-1β, IL-8, IL-17A and immunoglobulins of all three classes in urinary samples.The cohort of patients with GN selected for the study was divided in two groups (the main group and the comparison group). In addition to nephroprotective and steroid therapy, the treatment regimen of patients included rIL-2 in the main group, or cyclophosphamide in the comparison group. Regardless of the method used, the levels of protein, IgG and IL-17A in the urine proved to be decreased relative to the initial values; the contents of B cells and HLA-DR+ cytotoxic T lymphocytes in peripheral blood were found to be decreased. The revealed changes were more pronounced in the main group of patients. By 12 months after starting the treatment, the mentioned indexes began to differ significantly in the main group from those in the comparison group. Serum creatinine levels, numbers of T helper cells and Treg cells, IL-1β levels in urine did not undergo significant changes in the comparison group, whereas a decrease in serum creatinine and urinary IL-1β was registered in the main group of patients, along with decreased number of T helpers and increased numbers of Treg cells. In the main group of patients treated with rIL-2, the average number of relapses per year decreased by 4 times, showing only a 1.2-fold decrease in the comparison group. Hence, the low-dose therapy with rIL-2 may be considered an effective and safe alternative to conventional immunosuppressive therapy and a new option of the targeted treatment of glomerulonephritis with frequent recurrence of nephrotic syndrome.